1987
DOI: 10.1093/oxfordjournals.humrep.a136573
|View full text |Cite
|
Sign up to set email alerts
|

Lead, magnesium, selenium and zinc in human seminal fluid: comparison with semen parameters and fertility

Abstract: The concentrations of lead, magnesium, selenium and zinc in seminal fluid from men with variable semen quality (sperm morphology, density and motility) and fertility were determined by atomic absorption spectrometer without or with Zeeman background correction. The mean (+/- SD) concentration of selenium in the samples (n = 142) was 28.8 +/- 9.5 micrograms/l, which was about a third of the corresponding serum value (77.8 +/- 13.3 micrograms/l, n = 140). The serum selenium level was significantly (P less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
3
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 0 publications
6
53
3
2
Order By: Relevance
“…Other semen analysis variables, such as motility, viability and morphology, were not significantly correlated with SP zinc concentration. The results were similar to most reports in the literature [9,10,[31][32][33]. However, some studies have shown that a higher level of SP zinc may be associated with asthenozoospermia.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Other semen analysis variables, such as motility, viability and morphology, were not significantly correlated with SP zinc concentration. The results were similar to most reports in the literature [9,10,[31][32][33]. However, some studies have shown that a higher level of SP zinc may be associated with asthenozoospermia.…”
Section: Discussionsupporting
confidence: 91%
“…2.9 ± 1.7 3.0 ± 1.5 Total seminal zinc (µmol per ejaculate) 9.6 ± 5.5 10.9 ± 6.1 Abstinence (days) 3.7 ± 1.8 3.7 ± 2.2 Semen volume (mL) 3.6 ± 1. npg which further supports the earlier reports [9][10][11][12][13]27]. Currently, the fact that SP zinc concentrations are consistently correlated with sperm counts is poorly understood.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A positive relationship was demonstrated between low-dose environmental exposure to lead and unexplained poor sperm parameters and/or a decrease in male fertility (Saaranen et al, 1989 andLee et al 1992). Allowable safe concentrations of toxic pollutants are still a debatable issue in developing countries where there is wide variation in human susceptibility and tolerance, which depend on general human health and other environmental factors (WHO, 1977).…”
Section: Discussionmentioning
confidence: 99%